2013
DOI: 10.1007/s00428-013-1415-3
|View full text |Cite
|
Sign up to set email alerts
|

ERG expression and prostatic adenocarcinoma

Abstract: ERG gene rearrangement has been identified as a highly specific alteration that is present in 40-50 % of prostate carcinomas. The standardization of an immunohistochemical assay with a novel anti-ERG antibody recently described would have significant diagnostic value. The aims of this study were to identify the incidence of this rearrangement in a Spanish population and to test the specificity of immunohistochemical ERG evaluation for prostate carcinomas. Three prostate tissue microarrays were constructed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…Also in the preliminary analysis of the present study, and with similar sample size to that of the van Leenders et al study, we were not able to detect a relationship between ERG and grade, which became evident when the study group expanded. Verdu et al [13] found that 49% of Spanish PCs show ERG positivity. In their material no relationship with Gleason grade or stage was present.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the preliminary analysis of the present study, and with similar sample size to that of the van Leenders et al study, we were not able to detect a relationship between ERG and grade, which became evident when the study group expanded. Verdu et al [13] found that 49% of Spanish PCs show ERG positivity. In their material no relationship with Gleason grade or stage was present.…”
Section: Discussionmentioning
confidence: 99%
“…They result in immunohistochemical ERG positivity, which does not seem to occur otherwise in carcinomas. Therefore, immunohistochemical evaluation of ERG may be a useful test to evaluate the possible prostatic origin of metastatic carcinomas …”
Section: Ten Key Markers For the Diagnosis Of Soft Tissue Tumoursmentioning
confidence: 99%
“…Therefore, immunohistochemical evaluation of ERG may be a useful test to evaluate the possible prostatic origin of metastatic carcinomas. 48,51,55 K I T KIT receptor tyrosine kinase is a key cell signalling molecule, also referred to as CD117. It becomes normally activated (phosphorylated) when binding of its ligand stem cell factor links together two KIT molecules which then cross-phosphorylate each other's KIT tyrosine kinase domain, making it ready to phosphorylate downstream targets in the KIT signal transduction cascade.…”
Section: D 3mentioning
confidence: 99%
“…On immunostaining, 33% to 61% of all prostatic carcinomas are shown to be immunoreactive for ERG (Figure 5). 23,24,26,29-33 When positive, practically all neoplastic cells are labeled strongly. There is excellent correlation of ERG immunohistochemistry with presence of ERG gene fusion.…”
Section: Erg (Ets-related Gene)mentioning
confidence: 99%